2017
DOI: 10.1016/j.ejps.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation, controlled release, and antitumor efficacy of cisplatin delivered in liposomes composed of sterol-modified phospholipids

Abstract: We employed a recently introduced class of sterol-modified lipids (SML) to produce m-PEG-DSPE containing liposome compositions with a range of cis-platinum content release rates. SML have a cholesterol succinate attached to the phosphatidylglycerol head group and a fatty acid at the 2 position. These compositions were compared to the well-studied liposome phospholipid compositions: mPEG-DSPE/Hydrogenated Soy PC/cholesterol or mPEG-DSPE/POPC/cholesterol to determine the effect of the cis-platinum release extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
4
31
0
Order By: Relevance
“…The bags were then immersed in 100 mL of PBS and stirred (200 rpm, room temperature). At different time points (0, 1,2,3,8,12,18,24,30,36,42, and 48 h), 1 mL of PBS was collected to determine Cispt concentration using AAS method and replaced with 1 mL of fresh PBS. Cumulative drug release percentage was calculated using the formula below:…”
Section: Drug Release Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The bags were then immersed in 100 mL of PBS and stirred (200 rpm, room temperature). At different time points (0, 1,2,3,8,12,18,24,30,36,42, and 48 h), 1 mL of PBS was collected to determine Cispt concentration using AAS method and replaced with 1 mL of fresh PBS. Cumulative drug release percentage was calculated using the formula below:…”
Section: Drug Release Studymentioning
confidence: 99%
“…The results showed that the nanoparticles caused a significant reduction in the tumor volume compared to when Cispt was used (tumor volumes of 0.68 and 0.3 cm 3 in Cispt and Cispt-loaded NDAT nanoparticles receiver animals, respectively). Liposome nanoparticles are another delivery system, which are widely used for the treatment of cancer in in vitro and in vivo environments [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The CDDP-loaded sialyl Lewis X-modified liposomes (CDDP-SLX-LIP) were constructed and optimized. Liposomes had extended higher drug release and were gradually accumulated inside the tumour cell [84]. Vhora et al reported that the sterol cisplatin-based liposome demonstrated the greater half-life as a match free drug.…”
Section: Liposomesmentioning
confidence: 99%
“…Encapsulation of chemotherapeutics in nanocarriers, such as liposomes [6,7], nanoparticles [8,9], dendrimers [10,11] or micelles [12,13], which exploit the enhanced permeability and retention (EPR) effect, is the most extensively explored strategy for improving tumor bioavailability and reducing exposure to healthy tissues. However, these systems have had limited success, and only a small fraction (less than 1%) of the injected dose accumulates within the tumor, even in highly permeable tumors [14].…”
Section: Introductionmentioning
confidence: 99%